Juridical Analysis of the Implementation of Land Mafia Eradication - Majid, Abdul (TABELLIUS: Journal of Law, 2023)
Land mafia is a serious problem that can harm society and the country. As a serious problem, the law, which is a state instrument in national land planning which is mandated to be able to eradicate the land mafia, has not been implemented optimally. This is proven by the increasing number of land mafia cases, including in the Indramayu Regency area. This paper uses a type of sociological or empirical legal research method which includes legal identification and legal effectiveness. Empirical legal research is legal research in which data is obtained through primary legal data or data obtained directly in society. Keywords: Eradication; Juridical; Land; Mafia.